KEBIJAKAN PENGEMBANGAN PENDIDIKAN - Muhaemin B (Al-Ishlah: Jurnal Pendidikan Islam, 2017)
The development of education in Indonesia is currently faced with the moral problems of the nation's children. This study aims to provide constructive results for the national education system in terms of character education of the nation. This research uses descriptive method to collect actual information in detail that describe the existing symptoms, identify problems, make comparisons or evaluations. This study shows that any morality-related issues of education can not be solved using only one approach but require another approach depending on the conditions prevailing at the time.Indonesia’s national education system developed from the struggle for independence and the renaissance of the nation. During its development, many influences, local or global, contributed to the changing nature of the curriculum, pedagogy, assessment, and teacher professionalism. The author argues that education reform should entail a dialog involving the government, educators, and society to attain the goal of constructing an independent society of democracy and social justice.